Analisis Mekanisme Penyelesaian Konflik Norma Peraturan Menteri Terhadap Undang-Undang: Urgensi Rekonstruksi Pengaturan - Saputra, Adam Tri (Samsara Institute Publisher, 2025)
This study aims to examine the juridical construction related to the mechanism for resolving norm conflicts within the Indonesian legal system, as well as to formulate strategies to strengthen mediation mechanisms in resolving norm conflicts in the future. The existence of differences in regulatory substance between Law Number 12 of 2011 in conjunction with Law Number 13 of 2022 and the Regulation of the Minister of Law and Human Rights Number 2 of 2019 has created ambiguity in determining the authority of institutions responsible for resolving norm conflicts between ministerial regulations and laws. This research employs a normative method with statutory and conceptual approaches. The findings indicate that the current regulations regarding mechanisms for resolving norm conflicts within Indonesia's legal system remain inconsistent, resulting in legal uncertainty. Therefore, regulatory reconstruction is necessary to develop a robust, consistent, and procedural norm conflict resolution mechanism.